Care management from the perspective of supervising nurses - Maria Antônia Ramos Costa; Verusca Soares de Souza; João Lucas Campos de Oliveira; Elen Ferraz Teston; Laura Misue Matsuda (Rev Rene)
Objective: to understand the perceptions of supervising nurses on care management practices and, collectively, build a concept. Methods: qualitative study, conducted with 15 supervising nurses. The Freire’s Culture Circle was used as a data collection technique. The meetings were recorded, transcribed and analyzed according to their thematic structures. Results: through the individual concept, care management was considered as a complex responsibility, focused on bureaucratic actions. The collective concept related management with systematization of care that results in a comprehensive and qualified care. Concerning the difficulties in care management, aspects related to the institution were highlighted, such as the lack of standardization of norms and routines, physical structure and human resources. Conclusion:nurses perceive management and care in a fragmented way and the construction of a collective concept has resulted in the concern with the systematization and organization of the material, physical and human resources necessary for care.